2021
DOI: 10.22201/ib.20078706e.2021.92.3468
|View full text |Cite
|
Sign up to set email alerts
|

New records of oribatid mites (Acari: Oribatida) from a Patagonian forest affected by wildfire in Argentina

Abstract: Taxonomy and Systematics New records of oribatid mites (Acari: Oribatida) from a Patagonian forest affected by wildfire in ArgentinaNuevos registros de ácaros oribátidos (Acari: Oribatida) de un bosque patagónico afectado por fuego en Argentina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…The α-diversity, β-diversity and γ-diversity of mite communities are influenced by large-scale environmental factors, such as geographic location, natural hazards and climate [56][57][58] and are also limited by microhabitats such as lichens, mosses, bark and soil surfaces [59]. It was found that the number of individuals and family taxa of mites in the microhabitat of mosses was richer and the community characteristics were more The α-diversity, β-diversity and γ-diversity of mite communities are influenced by large-scale environmental factors, such as geographic location, natural hazards and climate [56][57][58] and are also limited by microhabitats such as lichens, mosses, bark and soil surfaces [59]. It was found that the number of individuals and family taxa of mites in the microhabitat of mosses was richer and the community characteristics were more prominent than in the environments of soils [60] and forests [61], which are also the study area of rocky desertification.…”
Section: Diversity Of Epilithic Moss Mites In Different Rock Desertif...mentioning
confidence: 99%
“…The α-diversity, β-diversity and γ-diversity of mite communities are influenced by large-scale environmental factors, such as geographic location, natural hazards and climate [56][57][58] and are also limited by microhabitats such as lichens, mosses, bark and soil surfaces [59]. It was found that the number of individuals and family taxa of mites in the microhabitat of mosses was richer and the community characteristics were more The α-diversity, β-diversity and γ-diversity of mite communities are influenced by large-scale environmental factors, such as geographic location, natural hazards and climate [56][57][58] and are also limited by microhabitats such as lichens, mosses, bark and soil surfaces [59]. It was found that the number of individuals and family taxa of mites in the microhabitat of mosses was richer and the community characteristics were more prominent than in the environments of soils [60] and forests [61], which are also the study area of rocky desertification.…”
Section: Diversity Of Epilithic Moss Mites In Different Rock Desertif...mentioning
confidence: 99%